Current trends and research opportunities in hybrid additive manufacturing - Dilberoglu, Ugur M.; Gharehpapagh, Bahar; Yaman, Ulas; Dolen, Melik (International journal of advanced manufacturing technology, 2021)
Despite the rapid growth in the past decade, the industrial adoption of additive manufacturing has not still been achieved due to certain limitations. A recent trend to alleviate its inherent drawbacks is to integrate additive manufacturing with secondary production techniques. Indeed, hybrid additive manufacturing solutions may help overcome the current barriers to today’s production systems by making use of the combined merits of merging technologies. This paper presents a comprehensive review of the current state-of-the-art in the field, covering the following three key aspects of the subject: (i) advances in the hybridization of additive manufacturing processes, (ii) developments in process planning for integrated technologies, and (iii) insights into the hybrid additive manufacturing industry. The main objective of the paper is to classify the latest knowledge for the researchers, along with highlighting challenges and future research directions in this field.